Kekurangan energi makanan tidak berefek negatif terhadap pertambahan tinggi badan laki-laki usia 18-21 tahun: Studi di Akademi Angkatan Laut Surabaya - Mega I D Ayu; Myrtati D Artaria (Masyarakat, Kebudayaan dan Politik, 2014)
This research was carried out to know increase of growth of males attending Indonesian Naval Academy in order to found the normal growth of healthy males for reference of Indonesia population, especially those in 18 to 21 years age. The variables measured were body height, weight, grip strength, and subscapular, biceps, triceps, and suprailiac skinfold thicknesses, while undergoing the first year of training. This research also analysed the difference between more activities and less activities group, while they were given the same kind and amount of food every day. The sample consisted of 50 male cadets aged 18-21 years. The sample was divided into two groups. Group 1: the group that was enrolled in CC (Cross Country) extra-curricular activity, and Group 2: the group that did not enrol in CC (Cross Country) extra-curricular activity. The two groups experienced the same treatment of basic physical exercises, and both received the same quality and amount of food every day. The Group 1 was arranged to get several additional hours of training in the morning and in the afternoon, related to the CC activities. The individuals within the two groups were measured twice—at the beginning of their training year, and a year later. Paired Sample T Test was used in seeing the difference between the two measurements. This research revealed that the physical exercise that was carried out in the Naval academy for a year did not cause any significant increases in the right and left grip strength of both groups. Both of the groups had a high intensity of physical exercise, consequently the significant declined in skinfold thicknesses. A difference in the increase of weight after a year was found between the two groups. The unsignificant increase of weight was found in Group 1. This was caused by the fact that they were subjected to extra physical training compared to Group 2. Although individuals in Group 1 were having tougher training, evidently they experienced significant increase in body height. Moreover, Group 1 experienced that significant increase in body height even though they did not experience significant increases in body weight. The increase of body height in the two groups possibly was caused by the fact that they were still at the age of growth in length. It might as well caused by good nutritive supplies throughout the year, and regular workouts. A further study comparing the cadets with common people must be carried out to further understand the influence of physical exercise and nutritive supplies to the increase of body height among males within the range of this age group.